Da esfera privada à realização cinematográfica: a chegada das mulheres latino-americanas ao posto de diretoras de cinema - Tedesco, Marina Cavalcanti (Universidade de São Paulo | Escola de Comunicações e Artes, 2012)
This article presents the initial results from a big research about women filmmakers in Latin America. Such results are: a literature review concerning women’s struggle for civil rights in the 19th and 20th centuries – it’s crucial to understand when women filmmakers emerge and why it happens – and what sources are available to usage in this research’s next steps.